2015
DOI: 10.2147/jpr.s71959
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia patients have reduced hippocampal volume compared with healthy controls

Abstract: ObjectiveFibromyalgia patients frequently report cognitive abnormalities. As the hippocampus plays an important role in learning and memory, we determined whether individuals with fibromyalgia had smaller hippocampal volume compared with healthy control participants.MethodsT1-weighted structural magnetic resonance imaging (MRI) scans were acquired from 40 female participants with fibromyalgia and 22 female healthy controls. The volume of the hippocampus was estimated using the software FreeSurfer. An analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…Anatomofunctional changes have also been reported in patients with chronic pain in the amygdala, 22,42,51 including decreases in gray matter volume, 15,53 increases in fractional anisotropy, 53 and alterations of power spectral density of low frequency. 42 Finally, studies have also reported FM-related changes in the hippocampus, including hippocampal atrophy, 55 reduced activation during a cognitive performance task, 54 reduced levels of N-acetyl aspartate, a measure of neuronal integrity, 4 as well as reduced binding potential for m-opioid receptor ligands. 36 Our study further uncovers a link between altered functional response in the MTL in FM patients and their experience of PAS.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomofunctional changes have also been reported in patients with chronic pain in the amygdala, 22,42,51 including decreases in gray matter volume, 15,53 increases in fractional anisotropy, 53 and alterations of power spectral density of low frequency. 42 Finally, studies have also reported FM-related changes in the hippocampus, including hippocampal atrophy, 55 reduced activation during a cognitive performance task, 54 reduced levels of N-acetyl aspartate, a measure of neuronal integrity, 4 as well as reduced binding potential for m-opioid receptor ligands. 36 Our study further uncovers a link between altered functional response in the MTL in FM patients and their experience of PAS.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, neuroimaging studies have shown augmented responses to a variety of painful stimuli in FM[15; 25; 56], and altered brain structure, metabolic activity and resting state functional connectivity in regions that are consistently involved in processing pain, e.g. [23; 28; 34; 36; 38; 44; 50; 57; 58; 60; 61]. …”
Section: Introductionmentioning
confidence: 99%
“…As noted above, an additional analysis including these participants was recently published by our group (McCrae et al, 2015). None of the analyses included here overlap with those in the previous report.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown hippocampal volume reductions in fibromyalgia patients (Lutz et al, 2008) and chronic insomnia patients (Riemann et al, 2007) separately. In addition, we recently reported results of a structural analysis indicating lower hippocampal volume bilaterally in a mixed cohort of patients with fibromyalgia and fibromyalgia with comorbid insomnia (McCrae et al, 2015). However, not all authors have replicated these results in insomnia (Winkelman et al, 2010) or other pain-related conditions such as frequent migraines (Maleki et al, 2013) and osteoarthritis (Mutso et al, 2012).…”
mentioning
confidence: 99%